Rocket Stove sebagai Solusi Alternatif Pengelolaan Sampah Rumah Tangga di Desa Batu Licin - Rizki Syapranata; M Rusydi; Salsabila Fatiha3; Dea Dwi Agustin4; Muhammad Saddam Alfandi; Muhammad Zulkifli; Alvira Oktavia Jasmon; Febri Aulyandra; Samsinar Samsinar; Candra Arwanti (Pusat Riset dan Inovasi Nasional, 2025)
The problem of waste in rural areas is still a serious issue that has an impact on environmental health and the quality of life of the community. Batu Licin Village, Gunung Lengkuas Village, East Bintan District, Bintan Regency is one of the areas that faces similar problems, where household waste is still scattered and has not been handled optimally. This community service activity offers innovative solutions through the manufacture of rocket stoves as a means of efficiently burning certain organic and inorganic waste, as well as the construction of garbage booths as a place to store and sort waste before further processing. The implementation method involves counseling to residents, making prototypes, and direct practice of using rocket stoves and garbage booths by local communities. In addition, this activity also emphasizes the importance of changing community behavior in managing waste with the 3R (reduce, reuse, recycle) principle. The results of the activity show an increase in public awareness in managing waste independently, reducing the accumulation of waste in the village environment, and the emergence of alternative waste processing that is environmentally friendly, energy-efficient, and easy to apply. This innovation not only helps overcome the problem of household waste, but also provides educational value and empowers the community in maintaining the cleanliness and sustainability of the village environment. With the implementation of rocket stoves and garbage booths, it is hoped that a cleaner, healthier, and more viable village environment will be created in the long term.